COBIB.SI: prirast bibliografskih zapisov v letu 2019 - Dornik, Ema (Organizacija znanja, 2020)
In Slovenia, 301 libraries and 689 cataloguers with permits for shared cataloguing of monographs participate in shared cataloguing. The article presents the annual increment of bibliographic and authority records in COBIB.SI in 2019. The increment data is collected from the shared database during the entire observed year. All the days of the year and all the records contributed by 575 cataloguers from 254 libraries are included in the analysis. The annual, monthly and daily increment data is presented. In 2019, 176,021 bibliographic records were contributed to COBIB.SI, and 60,068 authority records for personal names and for corporate bodies were contributed to CONOR.SI. The largest number of bibliographic records (28.7%) was created in the last quarter of the year. On a daily basis, the number of created bibliographic records was largest on Tuesday, 26 November 2019, when 1,022 bibliographic records were created. At the annual level, Tuesdays are the most productive days. In June and August, the numbers of created records were the smallest. In view of the record type, the trend of the past several years continues: most records were created for monographs (51.2%) and component parts (38.1%). The data on bibliographic and authority records downloaded from other databases is presented, too. In 2019, 645 persons actively participated in the creation of bibliographic and authority records in Slovenia. As 2.3% of bibliographic records were created on work-free days, it can be concluded that cataloguers are more and more in demand; 30.9% of cataloguers have two or more usernames, meaning that they work in more than one organisation. The analysis results of COBIB.SI increment presented indicate the importance of cataloguing in the COBISS system.
Keywords: 2019; annual increment; bibliografske baze podatkov; bibliographic databases; cataloguing; COBIB.SI; katalogizacija; letni prirast